Study on Eccentric Compression Behavior of Precast Stratified Concrete Composite Column with Inserted Steel Tube - Yilin Wang; Shikun Ma; Shunyao Wang (Buildings)
In order to improve the technical economy of steel-reinforced concrete structures and to promote the development of prefabricated concrete structures, a new type of partial precast steel-reinforced concrete column (precast stratified concrete composite column with inserted steel tube, PSCCST column) was proposed and studied in this paper. Six PSCCST column specimens were tested to investigate their behavior under eccentric loading. The failure state, ultimate bearing capacities, load–strain relationship, as well as load-deflection curves were emphatically investigated. The failure modes of the PSCCST columns under eccentric compression and corresponding bearing capacity Nu calculation methods were proposed based on experimental research and analysis. The results of the study indicated that there are three main failure modes, which are compressive-type failure mode, total-yield-type failure mode, and tensile-type failure mode. The first two modes are preferable due to their more effective material utilization. The Nu of the PSCCST column was found to decrease obviously with the increase of eccentricity e. The deformation capacity denoted by the horizontal lateral deflection corresponding to Nu increased with the increase of e. Moreover, the proposed Nu calculation methods were proven to have high accuracy by the comparison with the experimental results (the average ratio of the calculated values to the experimental values was 0.95).